Effect of Homoarginine on Coronary Artery Complexity and Atherosclerotic Burden in Patients with STEMI - Bingol, Gulsum; Huraibat, Ahmad; Govdeli, Elif Ayduk; Ser, Ozgur Selim; Unlu, Serkan; Celik, Murat; Bulut, Leyla; Ozden, Ozge; Ozmen, Emre; Kilickesmez, Kadriye (MDPI, 2025)
Objective: Homoarginine is a cationic amino acid derived from lysine. Evidence indicates that low-circulating homoarginine concentration is a risk factor for cardiovascular disease and all-cause mortality. A reduction in homoarginine concentrations has been observed in patients with ischemic heart disease, ischemic stroke, ischemic heart disease, and heart failure. The SYNTAX score (SS), an angiographic scoring system, defines the grade and complexity of coronary artery disease (CAD). The objective of this study was to evaluate the relationship between homoarginine level and the severity of CAD according to the SYNTAX score in patients with ST-segment elevation myocardial infarction (STEMI). Methods: A total of 67 subjects were enrolled into the study with the diagnosis of STEMI of those who underwent coronary angiography. STEMI patients were divided into two groups: low-medium SYNTAX score 14 (32 patients). Results: Within the high SS group, serum homoarginine levels were markedly lower (2 +/- 0.9 vs. 1.3 +/- 0.7; p = 0.001). Homoarginine levels and SS showed a significant negative correlation in entire study cohort In multivariate regression analysis, serum homoarginine levels along with serum urea levels were significantly associated with having higher SS (OR 1.073 p = 0.049 and OR 0.346, p = 0.012, respectively). Conclusions: In conclusion, the diminished plasma homoarginine level emerges as an independent predictor of high atherosclerotic burden among STEMI patients. To the best of our knowledge, this is the first study to demonstrate the relationship between homoarginine and coronary artery complexity.
Keywords: atherosclerosis; complex coronary artery disease; coronary artery disease; homoarginine; SYNTAX score; ST-segment elevation myocardial infarction; SIROLIMUS-ELUTING STENT; CARDIOVASCULAR RISK; CLINICAL-OUTCOMES; ARGININE; PREDICTION; MORTALITY; General & Internal Medicine